Identification of a Potential SNP Related to the Expression of Immune Genes and Its Possible Application to Selection of WSSV-Resistant Pacific White Shrimp (Litopenaeus vannamei) - Bagus Rahmat Basuki; Alimuddin Alimuddin; Dinar Tri Soelistyowati; Sri Nuryati (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research A molecular marker for shrimp selection in disease resistance. Single nucleotide polymorphisms (SNP) in the ALF gene strongly correlate with shrimp resistance to WSSV infection. Higher ALF gene expression in survivor shrimp. SNP as molecular marker inherited in the first generation (G1) shrimp. ARMS-PCR method successfully detect SNP in the shrimp ALF gene. Abstract The Pacific white shrimp (Litopenaeus vannamei) is Indonesia's main export commodity, but its production is constrained by the white spot syndrome virus (WSSV). Selective breeding of disease-resistant broodstock based on single nucleotide polymorphism (SNP) in the anti-lipopolysaccharide factor (ALF) gene is an alternative strategy for solving the disease problem. This study aimed to detect the SNP g.455 A>G in the anti-lipopolysaccharide factor (ALF) shrimp gene, evaluate the correlation of SNP with WSSV-resistance trait, analyze the expression level of immunity genes and genotype frequencies of the WSSV-resistance population shrimp and analyze the SNP inheritance in the first generation of selected shrimp. A total of 120 individuals from 4 families were used to detect the SNP marker using tetra-primer amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). The correlation of the SNP marker with survival rate (SR) was analyzed using a general linear model (GLM) between genotype frequencies and SR. Genotypic similarities between broodstock and pedigree were analyzed using Chi-square. SNP g.455 A>G was successfully detected using the ARMS-PCR method and had a strong correlation between the marker and SR (p-value of AA = 0.012; AG = 0.359, and GG = 0.001). The resistant population has significantly higher ALF and SOD gene expression levels and AA genotype frequency. The SNP marker was inherited, so the broodstock and pedigree have the same genotype frequencies according to chi-square analysis (Ï‡2 = 0.46 and p-value = 0.497). These results suggested that the g.455 genotype AA could be selected to produce WSSV-resistant Pacific white shrimp.